IKN: West Kalimantan's Golden Bridge of Sharia Economy Towards The International Market - Helvira, Reni (Journal of Islamic Economy, 2024)
This study explores the potential of the development of the National Capital City (IKN) in East Kalimantan as a catalyst for the development of the sharia economy in West Kalimantan (Kalbar) in order to expand access to the international market. As a country with the largest Muslim population in the world, Indonesia has a great opportunity to optimize the sharia economy, which continues to grow significantly at the global and national levels. West Kalimantan, with its rich natural resources and strategic geographical position, has strong potential to become a regional center for the sharia economy. However, challenges such as low sharia financial literacy and limited connecting infrastructure still hinder the optimization of this potential. This study uses a descriptive qualitative method with a phenomenological approach to understand the perspectives of key stakeholders, including local governments, sharia entrepreneurs, and sharia finance practitioners in West Kalimantan, regarding the impact of the development of the IKN on the sharia economy. Data were collected through in-depth interviews, participant observation, and analysis of related documents. The results of the study show that the development of the IKN opens wider access for West Kalimantan's sharia products and services to enter the international market, especially through increasing infrastructure connectivity and synergy with neighboring countries that have a strong sharia economic base, such as Malaysia and Brunei Darussalam. This study makes an important contribution in filling the knowledge gap regarding the relationship between infrastructure development and the internationalization of the sharia economy. In addition, the results of this study can be a reference for policy makers in designing effective strategies to make West Kalimantan a leading center for the sharia economy in Southeast Asia, utilizing the momentum of the IKN development to open up new opportunities in the global market